2005
DOI: 10.2214/ajr.184.3.01840832
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor in Hepatocellular Carcinoma and the Surrounding Liver and Correlation with MRI Findings

Abstract: Our results indicate that the signal intensity and heterogeneity of hepatocellular carcinomas on MR images correlate with the degree of VEGF expression in hepatocellular carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
1
22
0
2
Order By: Relevance
“…134 In fact, blood vessel density and VEGF expression correlate directly with Child-Pugh score and the proliferative index, size and grade of HCC tumours. [135][136][137][138][139][140] A number of chemokines and their receptors are upregulated in the diseased liver and peripheral blood in the progression of liver fibrosis to cirrhosis and in the pathogenesis of malignant HCC. These molecules regulate inflammation, fibroproliferation, angiogenesis, carcinogenesis, metastasis, and anti-tumour immunity.…”
Section: Activatedmentioning
confidence: 99%
“…134 In fact, blood vessel density and VEGF expression correlate directly with Child-Pugh score and the proliferative index, size and grade of HCC tumours. [135][136][137][138][139][140] A number of chemokines and their receptors are upregulated in the diseased liver and peripheral blood in the progression of liver fibrosis to cirrhosis and in the pathogenesis of malignant HCC. These molecules regulate inflammation, fibroproliferation, angiogenesis, carcinogenesis, metastasis, and anti-tumour immunity.…”
Section: Activatedmentioning
confidence: 99%
“…Vascular properties of tumour tissue can be quantified by assessing the kinetics of the contrast agent [7,8]. Pharmacokinetic (PK) modelling can be used to provide quantitative information such as the volume transfer rate (k trans ) and extravascular extracellular volume fraction (v e ); these model parameters provide information about perfusion and permeability of tumour vasculature [5] and have been found to be related to prognostic factors [9]. As tissue vasculature can be assessed by DCE-MRI, its role in assessing antiangiogenic and anti-vascular therapies is increasing [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus infection may induce HCC in the absence of liver cirrhosis, while in patients with C virus hepatitisthe cirrhosis underlies all future pathologies. The inverse correlation between hepatic arterial vascularity and the expression of the VEGF level in HCV related HCC patients was found by Kanematsu et al [36], contrary to the experiences of Kwak et al [19] who found a positive correlation in the study of mostly HBV related HCC patients. Kanematsu justifiedthe divergence by the substantial differences in the Japanese patient's population and in the underlying hepatic disease.…”
Section: Discussionmentioning
confidence: 56%
“…Such observations could indicate either an inverse correlation between serum VEGF levels and various clinical and laboratory variables indicating advances of HCC or no correlation at all, as it is suggested, for instance, by Chen and his co-workers [35]. It should be noted, however, that most of the presented data on VEGF and HCC significant correlation originate from Chinese research centers, where HCC is frequently related to hepatitis B virus infection [22,36,37]. In our patients HCC tended to be related to HCV virus infection.…”
Section: Discussionmentioning
confidence: 99%